Dangerous Liaison: Helicobacter pylori, Ganglionitis, and Myenteric Gastric Neurons: A Histopathological Study. (30th December 2019) - Sticlaru, Liana; Stăniceanu, Florica; Cioplea, Mirela; Nichita, Luciana; Bastian, Alexandra; Micu, Gianina; Popp, Cristiana
Abstract : Chronic inflammation induced by Helicobacter pylori ( H. pylori ) infection plays a major role in development of gastric cancer. However, recent findings suggested that progression of inflammation and neoplastic transformation in H. pylori infection are more complex than previously believed and could involve different factors that modulate gastric microenvironment and influence host-pathogen interaction. Among these factors, gastric myenteric plexus and its potential adaptive changes in H. pylori infection received little attention. This study is aimed at identifying the impact of H. pylori -associated gastritis on number and morphology of nerve cells in the stomach. The distribution of density, inflammation, and programmed cell death in neurons was immunohistochemically assessed in full-thickness archival tissue samples obtained from 40 patients with H. pylori infection who underwent surgery for gastric cancer and were compared with findings on samples collected from 40 age- and sex-matched subjects without bacteria. Overall, significant differences were noted between H. pylori -positive and H. pylori -negative patients. The analysis of tissue specimens obtained from those with infection revealed higher density and larger surface of the myenteric nervous plexus, as well as a significant increase in the number of gastric neuronal cell bodies and glial cells compared to controls. A predominant CD3-immunoreactive T cell infiltrate confined to the myenteric plexus was observed in infected subjects. The presence of mature B lymphocytes, plasma cells, and eosinophils was also noted, but to a lesser extent, within the ganglia. Myenteric ganglionitis was associated with degeneration and neuronal loss. Our results represent the first histopathological evidence supporting the hypothesis that H. pylori -induced gastric inflammation may induce morphological changes in myenteric gastric ganglia. These findings could help gain understanding of some still unclear aspects of pathogenesis of H. pylori infection, with the possibility of having broader implications for gastric cancer progression.